Teen Titans. Trouble in Tokyo : [videorecording (DVD)] / original movie - Chang, Michael; Jones, Ben. active 1997; Youngberg, Matt; Cipes, Greg; Menville, Scott; Strong, Tara, 1973-; Walch, Hynden (Warner Home Video, 2007)
The Teen Titans journey to Japan to find the notorious villain Brushogun. But crushing the criminal element on the other side of the ocean isn't as easy as they thought. Now it's the law that is unintentionally aiding Brushogun in destroying them all!